Penyusunan Model untuk Penangkapan Berkelanjutan Ikan Pelagis dengan Pendekatan Jenjang Trofik di Selat Makassar - Kaswadji, Richardus; Hatta, Muhammad; Umar, Nur Asia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Observations on pelagic fish catch activities using bagan Rambo in Makassar Strait had been conducted in 2005and 2006 to obtain physical, chemical, and biological data and their processes in the operation of bagan Rambo inthe observation sites. The objective of the study was to overcome the overfishing problems which have beenhappenning in Makassar Strait, using a model of the trophic level approaches. Nine observation stations were setin three transects perpendicular to the coast. The measurement of physical, chemical, and biological parameterswere conducted monthly. Biological parameters measured were chlorophyll-a, and the abundance of phytoplanktonand zooplankton. Phytoplankton primary productivity, grazing mortality of phytoplankton by zooplankton, numberof catch of fish, and fish feeding habit were also measured. Run of the built model based on the data obtainedshowed that with the present catch-pressure (assuming that this was the start of catching operation), there wouldbe an overfishing starting in the 26 th or 27th month onward. Meanwhile, if the catch were half of the present, thenthere would be an overfishing in the 31 st or 32nd month, but would back to the sustainable production months afterthat. The model is still being developed by finding and adding more accurate data and parameters.